2017
DOI: 10.1016/j.cmi.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Potential economic burden of carbapenem-resistant Enterobacteriaceae (CRE) in the United States

Abstract: Objectives The Centers for Disease Control and Prevention considers carbapenem-resistant Enterobacteriaceae (CRE) an urgent public health threat; however, its economic burden is unknown. Methods We developed a CRE clinical and economics outcomes model to determine the cost of CRE infection from the hospital, third-party payer, and societal, perspectives and to evaluate the health and economic burden of CRE to the USA. Results Depending on the infection type, the median cost of a single CRE infection can ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
121
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(132 citation statements)
references
References 56 publications
(22 reference statements)
3
121
0
4
Order By: Relevance
“…The problem of carbapenem resistance in this pathogen is magnified by the paucity of options for the treatment of CRE [11], which may lead to inappropriate initial therapy [14]. At current rates, CRE infections are estimated to result in a 26% mortality rate and cost hospitals $275 million annually [2]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of carbapenem resistance in this pathogen is magnified by the paucity of options for the treatment of CRE [11], which may lead to inappropriate initial therapy [14]. At current rates, CRE infections are estimated to result in a 26% mortality rate and cost hospitals $275 million annually [2]. …”
Section: Discussionmentioning
confidence: 99%
“…Increasing resistance to carbapanems thus jeopardizes patient outcomes and results in a significant economic burden [2, 3]. The increased morbidity and mortality associated with antibiotic resistance is of particular concern in vulnerable populations such as patients in intensive care units (ICUs) [4].…”
mentioning
confidence: 99%
“…Those are the ambler molecular class A (KPC), class B (VIM, IMP and NDM) and class D (OXA‐48) types . The genes of these enzymes are located on plasmids and can be freely transferred between bacteria . Plasmids can carry also several resistance determinants, such as plasmid‐mediated quinolone resistance (PMQR) genes, that has been reported in gram negative bacilli including K pneumoniae in the past few decades all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…9 Horizontal transfer of plasmids has been identified as an important mechanism spread of multidrug resistance spread all over the world. 8 Early detection of multidrug resistance by rapid diagnostic techniques may limit their spread, particularly in hospitals. 10 Whilst many researchers have studied plasmids which carry qnr genes along with β-lactamase genes, 11,12 relatively, little is reported about the association between qnr genes and carbapenemase genes in resistant K pneumoniae strains.…”
mentioning
confidence: 99%
“…Moreover, CRE are considered an urgent public health threat, 3 and a single CRE infection in the United States can cost society up to $83,512. 4 Our previous work demonstrated that 1 part of the CDC CRE toolkit (ie, active screening of interfacility transfers with subsequent contact precautions) was better than measures currently used in most healthcare facilities (eg, contact precautions only for known carriers) in a region where CRE is newly emerging. 1 The CDC CRE toolkit can be implemented in 2 ways: in individual facilities or in a coordinated regional fashion.…”
mentioning
confidence: 99%